Theory of Planned Behavior as an Antecedent in Predicting Fraudulent Intentions of Academic Accountants and Non-Academic Accountants - Novi Lailiyul Wafiroh; Wuryaningsih Wuryaningsih (Universitas Negeri Malang, 2024)
Purpose: Individual behavior is a representation of what is believed. Likewise, an accountant intends to commit financial statement fraud. Related to predicting individual behavior to do or not to do something action can use the Theory of planned behavior (TPB). This research examines three main variables in TPB, attitude, subjective norms, and perceived behavioural control on academic and non-academic accountants' fraud intentions through the Theory of Planned Behavior (TPB) variables.Method: This research is quantitative, with primary data obtained from questionnaires sourced from respondents. Respondents were academic and non-academic accountants. The research sample was selected using a purposive sampling method with specific criteria. The partial least squares (PLS) method was used to analyze the data.Findings: The findings suggest that attitudes and subjective norms significantly positively affect the intention to commit financial statements fraud in academic and non-academic accountants, while perceived behavioural control does not significantly affect the intention to commit fraud in financial reporting.Originality/Value : Research that examines the intentions of academic accountants and non-academic accountants in committing financial statement fraud and studied using the theory of planned behavior is the first to be conducted.